Radiomic Analysis to Predict Outcome in Recurrent Glioblastoma Based on Multi-Center MR Imaging From the Prospective DIRECTOR Trial - Vils, Alex; Bogowicz, Marta; Tanadini-Lang, Stephanie; Vuong, Diem; Saltybaeva, Natalia; Kraft, Johannes; Wirsching, Hans-Georg; Gramatzki, Dorothee; Wick, Wolfgang; Rushing, Elisabeth; Reifenberger, Guido; Guckenberger, Matthias; et al. (Frontiers in Oncology, 2021)
Background: Based on promising results from radiomics approaches to predict MGMT promoter methylation status and clinical outcome in patients with newly diagnosed glioblastoma, the current study aimed to evaluate radiomics in recurrent glioblastoma patients. Methods: Pre-treatment MR-imaging data of 69 patients enrolled into the DIRECTOR trial in recurrent glioblastoma served as a training cohort and 49 independent patients formed an external validation cohort. Contrast-enhancing tumor and peritumoral ring volumes were segmented on MR images. 180 radiomic features were extracted after application of 2 MR intensity normalization techniques: fixed number of bins and linear rescaling. Radiomics feature selection was performed via principal component analysis and multivariable models were trained to predict MGMT status, progression-free survival from first salvage therapy, referred to herein as PFS2, and overall survival (OS). The prognostic power of models was quantified with concordance index (CI) for survival data and area under receiver operating characteristic curve (AUC) for the MGMT status. Results: We established and validated a radiomics model to predict MGMT status using linear intensity interpolation and considering parameters extracted from gadolinium-enhanced T1-weighted MRI (training AUC=0.670, validation AUC=0.673). Additionally, models predicting PFS2 and OS were found for the training cohort but were not confirmed in our validation cohort. Conclusions: A radiomics model for prediction of MGMT promoter methylation status from tumor texture features in patients with recurrent glioblastoma was successfully established, providing a non-invasive approach to anticipate patient’s response to chemotherapy if biopsy cannot be performed. The radiomics approach to predict PFS2 and OS failed.